Combining zeolite with MOF glass to construct crystal-glass composite membranes for improved hydrogen separation - Hongbin Wang; Caiyan Zhang; Lili Fan; Zixi Kang; Daofeng Sun (Advanced Membranes)
Metal-organic framework glasses (MOF-ag), formed through melt-quenching crystalline MOFs, have emerged as promising membrane materials owing to their processability and retained porosity. While MOF-ag membranes exhibit exceptional sieving selectivity, their compromised permeability has driven the development of crystal-glass composite (CGC) membranes, where crystalline porous fillers are embedded in MOF-ag matrices. Nevertheless, the high-temperature melt-quenching process poses a significant challenge to the thermal stability of porous fillers, inducing structural degradation of thermally labile fillers and severely compromising gas permeability. In this study, we report the rational design of FAU-type zeolite-embedded ZIF-62-ag composite membranes to improve hydrogen separation performance. The optimized 20-FAU-ZIF-62-ag CGC membrane (20 ​wt% zeolite filler loading) exhibits the H2 permeability of 2516 Barrer and H2/CH4 selectivity of 52.4 for single-gas permeation, representing 179 ​% and 45 ​% improvements over the pristine ZIF-62-ag membrane. The zeolite incorporation not only improves porosity but also enhances mechanical strength, evidenced by the enhanced Young's modulus (85 ​%) and hardness (55 ​%). Further processing with an alternative zeolite filler (MFI-type zeolite) or an alternative MOF-ag matrix (TIF-4) validates the universality of zeolite-MOF-ag CGC membranes in improving performance. This study provides a versatile platform for fabricating robust MOF-ag-based membranes with improved separation performance.